Public Private Partnership in Rajya Adarsh Vidyalaya Model Concession Agreement - Planning Commission (Planning Commission, 2014)
The Twelfth Plan lays special emphasis on the development of social sectors in view of their impact on human development and quality of life, especially of the less privileged families. Accordingly, the allocation for education constitutes 12.71 percent of the Gross Budgetary Support in the Twelfth Plan. The objectives, physical targets and outcomes set out in the Twelfth Plan cannot be met out of public resources alone. It is, therefore, imperative that these resources are supplemented by the non-government sector with a view to ensuring that the targets set in physical as well as financial terms are met by the end of the Twelfth Plan period.
Planning Commission Government Of India
Planning Commission Government of India